A tool for assesing multiliteracy in higher educacation - Marzal , Miguel-Ángel; Borges , Jussara (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2020)
This study describes the premises underlying Voremetur, a project conducted in the context of higher education. It hypothesises the need to support a competence education method adapted to new educational formulas (from e- to m-learning), new educational challenges (e-science, big data) and the convergent competences now characterised as info-communication literacy, which has favoured the transition from edu-communication to multiliteracy. Such competences should be organised into competence programmes, where the assessment of the beneficial results for learners and the university should be included as an essential element. The article discusses an assessment model for new literacies, including its conceptual framework, ideal evaluation tools and conversion into an ad hoc questionnaire. Lastly, the paper describes model application to a target group and analyses the results most relevant to information behaviour. Keywords: Metaliteracy; Academic literacy; Information literacy; Info-communication literacy Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/9273/6082